Efficient in-vitro regeneration protocol in chrysanthemum (Chrysanthemum morifolium) from ray florets (Current Horticulture, 2023)
The experiment was conducted to standardize regeneration protocol from ray florets in chrysanthemum cv. Pusa Arunodaya (TQP 06). For callus induction, the highest callusing percent (82.67%) with a minimum number of days for callus initiation (10.87 days)  was observed in MS medium supplemented with Kinetin (10 mg/l) + NAA (1.0 mg/l) in treatment (T3). Highest shooting percent  (69.33 %) with minimum number of days for shoot initiation (6.27 days) along with maximum number of shoots per explant (5.67  shoots) in MS medium supplemented with Kinetin (5.0 mg/l) + NAA (1.0 mg/l). In shoot proliferation, the highest number of shoots  after 30 days (51.67), 60 days (72.00), and 90 days (98.67) in MS medium supplemented with Kinetin (5.0 mg/l) + NAA (1.0 mg/l).  The highest rooting percent (85.00%) with least days for root initiation (7.00 days) along with maximum roots per shoot (8.00) and  optimum root length (5.00 cm) in MS medium supplemented with IBA (0.2 mg/l). The rooted plants were successfully acclimatized  in 3-4 weeks and survived under field conditions.
Keywords: Chrysanthemum; in-vitro; ray florets; callus induction; regeneration; proliferation